Effect of Soil Salinity and Sodicity on Growth and Mineral Nutrition of some Poplar (Populus deltoides) Clones - Yadava, R. B.; Prakash, Om (Indian Forester, 1995)
A pot culture experiment was conducted from February to July, 1985 to study the growth and nutrient uptake of three important clones of poplar (Populus deltoides) viz. G-3, G-48 and D-121 under varying levels of artificially created salinity (control, 0.3, 0.6, 0.9 and 1.2 % soluble salts) and sodicity (control, 20, 40, 50, and 80 ESP) in a silty clay loam soil. The results revealed that none of the clones could survive in salinity conditions. In sodicit treatment also the three clones survived only upto pH 8.5 (ESP-20). Plant growth in terms of height, girth and biomass (both aboveground and belowground) decreased with the increase in soil sodicity. This adverse effect was variable among the clones. In G-3 and G-48, root growth was more affected while in D-121 reduction was mOl’e in shoot biomass. Nutrients content ofN, P, K, Ca and Mg decreased while Na content increased under sodic conditions resulting into higher Na/K, Na/Ca and Na/Mg ratios in all the three poplar clones.